Zircon U–Pb geochronology, mineral and whole‐rock geochemistry of the Khardung volcanics, Ladakh Himalaya, India: Implications for Late Cretaceous to Palaeogene continental arc magmatism. (24th July 2019) - Lakhan, Nongmaithem; Singh, Athokpam Krishnakanta; Singh, Birendra Pratap; Sen, Koushik; Singh, Mutum Rajanikanta; Khogenkumar, Shoraisam; Singhal, Saurabh; Oinam, Govind
Abstract : In this study, we present new mineral and whole‐rock geochemical data with zircon U–Pb ages of the Khardung volcanics (KV) from the western Himalaya and discuss their tectono‐magmatic evolution. These volcanics are sandwiched between the Ladakh batholith and Karakoram batholith and classified as intermediate volcanics (basaltic andesite‐andesite) and felsic volcanics (dacite‐rhyolite). The intermediate volcanics are marked by low SiO2 (52.80–61.31 wt.%), enriched LREEs, and depleted HFSEs (Nb, Ti, Zr), whereas more evolved felsic volcanics exhibit quartz, K‐feldspar, and plagioclase as dominant mineral phases and felsic compositions are characterized by high SiO2 (64.52–79.19 wt.%) content with pronounced negative Eu anomalies, enriched LREEs, and depleted HREEs and HFSEs (Nb, Ti). New zircon U–Pb ages of intermediate volcanics (andesite) yield 69.71 Ma, whereas felsic volcanics (rhyolites) range between 62.49 and 66.55 Ma, indicating that the Khardung magmatism overlaps with the last phase of the Ladakh batholith magmatism. Geochemical characteristics indicate that the KV were generated from a same parental magma source through fractional crystallization along with crustal assimilation from an older crust, and they show genetic affinity with the adjacent Ladakh batholith. Therefore, the KV and Ladakh batholith could be considered as a product of the mature stage arc magmatism generated during subduction of the Neo‐Tethyan oceanic crust prior to the main collision between the Indian and Eurasian continents.